2022
DOI: 10.3390/ani12243519
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inclusion of Former Foodstuff and Distiller Grains in Dairy Cows Ration: Effect on Milk Production, Rumen Environment, and Fiber Digestibility

Abstract: The aim of the present study was to investigate the effect of the substitution, in dairy cow rations, of traditional protein and starch sources with more sustainable “circular” feeds to increase the sustainability of dairy production. For this purpose, eight multiparous mid-lactating cows were blocked and assigned to one of four treatments and were used in a replicated 4 × 4 Latin squares design with 21-days periods (14 days of adaptation and 7 of data collection). Two different circular feedstuffs were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Statistically highly signifi cant (< 0.01) drop in milk fat content between 0 and 21 st day of our treatment with 25% of WDGS is not in compliance with the fi ndings of Kavitha et al (2021), who concluded that WDGS could be included up to 35% of DM requirement with no adverse eff ect on milk yield and composition of the crossbred cows for economical production. A similar positive statement was reported by Mammi et al (2022), who found out that the rational inclusion of wheat distillers in properly formulated rations represented a safe opportunity to reduce the environmental impact of dairy farming while maintaining high production levels.…”
Section: Discussionsupporting
confidence: 74%
“…Statistically highly signifi cant (< 0.01) drop in milk fat content between 0 and 21 st day of our treatment with 25% of WDGS is not in compliance with the fi ndings of Kavitha et al (2021), who concluded that WDGS could be included up to 35% of DM requirement with no adverse eff ect on milk yield and composition of the crossbred cows for economical production. A similar positive statement was reported by Mammi et al (2022), who found out that the rational inclusion of wheat distillers in properly formulated rations represented a safe opportunity to reduce the environmental impact of dairy farming while maintaining high production levels.…”
Section: Discussionsupporting
confidence: 74%
“…Analytical TMR analyses were performed at the University of Bologna feed analysis laboratory according to the methodology described in previous studies (Mammi et al. 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…They are generated from the oil extraction process, to meet the growing demand of the sectors: pharmaceutical; to feed; biofuels and cosmetics ( 4 ). The inclusion of these co-products in ruminant feed has been studied due to the levels of neutral detergent fiber, crude protein and energy, through the residual ether extract, and show promising results ( 5 8 ), including in combined inclusion ( 9 ).…”
Section: Introductionmentioning
confidence: 99%